Gestão organizacional e desempenho de pessoas: estudo diagnóstico sobre o alinhamento entre sistemas de avaliação em hospitais públicos - Nunes, Najara de Sena (2011)
Personnel and business performance management comprise the basic issue of Administration. In the medical and health services it takes an even greater dimension because of the complexities of healthcare facilities administration. The relation between business and personnel indicator systems is almost an axiom in the field of Administration, even though few researches have gone deep in analyzing this relation, the quality of which and its adherence is decisive for the success of strategic implementation initiatives. The objective of this research is to ascertain the alignment level between business performance indicators and personnel indicators in public hospitals in the city of Fortaleza - Ceará – Brazil. This study has a quantitative approach, and has adopted the transversal cut methodology to obtain a picture of the state of Ceará public hospitals, based on the study of a sample made up by the three biggest hospitals – on which the data was available – on the Fortaleza metropolitan area. The data was gathered among seven healthcare executives (Human Resources (HR) and financial) of the facilities under analysis, by means of diagnostic interviews (HOLANDA and FERRAZ, 2007) specially adapted for the hospital environment, and based on the traditionally accepted quality evaluation models of the GESPÚBLICA and FNQ. In addition, the data gathering and analysis explored a model structured in verification items, in the dimensions. Based on the diagnostic model used, the research findings identified several different situations in terms of the consolidation of strategic management practices and personnel performance management. Also, the alignment level between these two indicator systems, which is the key objective of this study, was investigated. This revealed that one of the facilities has a low level of alignment between both indicators, a second one is in a consolidation level and the third is in an advanced level of alignment. Furthermore, this research explores the singularities of each medical center and provides a final step where the results obtained are discussed with the interviewees, so as to give them a detailed knowledge of their strong points and what improvements can be done to orient the decision-making in their organizations in order to improve the management and health service quality provided by them. At the same time, it details a management tool that can be applied in other healthcare institutions.